Predictive estimates of climate changes in the Arctic based on the combined scenario - N.A. Diansky; I.V. Solomonova; A.V. Gusev (Российская Арктика, 2019)
The article proposes a combined scenario of climate changes estimates based on the composition of «greenhouse» and «cyclical» effects. With its use, the causes of climate fluctuations in the Arctic were diagnosed. The scenario of its change in the XXI century was clarified and was given the scenario of changing of the Arctic ice cover for the long term. The latter will provide an opportunity to assess the development prospects of the Northern Sea Route.